2020
DOI: 10.3389/fmed.2020.00193
|View full text |Cite
|
Sign up to set email alerts
|

Pain- and Fatigue-Related Functional and Structural Changes in Ankylosing Spondylitis: An fRMI Study

Abstract: Background: Chronic pain and fatigue are two cardinal features of ankylosing spondylitis (AS) and how to effectively treat these conditions continues to be a challenge. The underlying mechanisms and the relationship between AS-related pain and fatigue remain poorly understood. The present study was conducted, therefore, to explore the brain functional and structural changes associated with pain and fatigue in AS. Methods: A total of 65 AS patients (48 men and 17 women; 32.33 ± 8.6 years) and 53 age-and sex-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Results showed that communication of the SMN with the PMN and DMN was specifically associated with betweenparticipants variance in fatigue across the testing day, over and above the contribution of variance related to pain occurrence, pain disability and CIS-fatigue. This is in line with our hypothesis and previous reports on sensorimotor involvement in fatigue in multiple sclerosis (MS) (Hidalgo de la Cruz et al, 2018), stroke (De Doncker, Dantzer, Ormstad, & Kuppuswamy, 2018;Kuppuswamy, Rothwell, & Ward, 2015), perinatal stroke (Wrightson, Zewdie, Kuo, Millet, & Kirton, 2020) and ankylosing spondylitis (Liu et al, 2020) and generalize our previously reported task-related effects of fatigue (van der Schaaf et al, 2018) to resting-state connectivity. The lack of relationship with CIS-fatigue may relate to the low variability in CIS-fatigue scores as patients were selected to be severely fatigued on this score.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Results showed that communication of the SMN with the PMN and DMN was specifically associated with betweenparticipants variance in fatigue across the testing day, over and above the contribution of variance related to pain occurrence, pain disability and CIS-fatigue. This is in line with our hypothesis and previous reports on sensorimotor involvement in fatigue in multiple sclerosis (MS) (Hidalgo de la Cruz et al, 2018), stroke (De Doncker, Dantzer, Ormstad, & Kuppuswamy, 2018;Kuppuswamy, Rothwell, & Ward, 2015), perinatal stroke (Wrightson, Zewdie, Kuo, Millet, & Kirton, 2020) and ankylosing spondylitis (Liu et al, 2020) and generalize our previously reported task-related effects of fatigue (van der Schaaf et al, 2018) to resting-state connectivity. The lack of relationship with CIS-fatigue may relate to the low variability in CIS-fatigue scores as patients were selected to be severely fatigued on this score.…”
Section: Discussionsupporting
confidence: 94%
“…So far, only a few studies did compare pain and fatigue-related connectivity patterns within one patient population. Specifically, using graph theoretical measures a recent study assessed symptom-specific associations in patients with ankylosing spondylitis and showed a partial network-level dissociation between fatigue-and pain-related brain connectivity (Liu et al, 2020). While functional connectivity of the DMN nodes with the rest of the brain was associated with both pain and fatigue, connectivity of the pre-central gyrus (part of the SMN) and superior parietal gyrus were only associated with fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…, cognitive coping strategies and attentional distraction) in ONFH patients. In addition, functional and structural changes in the PFC, including ankylosing spondylitis ( Liu et al, 2020 ), irritable bowel syndrome ( Mao et al, 2020 ), chronic lower back pain ( Yu et al, 2020 ), and neuropathic pain ( Li et al, 2020 ), have been demonstrated in other pain studies. In a recent rs-fMRI study ( Feng et al, 2020 ), researchers revealed an abnormal pattern of brain activity in ONFH patients and found that the most significant increase in ALFF occurred in pain-related brain regions, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…These regions include the sensory/somatomotor network (SMN), dorsal attention network (DAN), and task control network (TCN). Changes in brain activity and connectivity within these networks may contribute to the experience of fatigue in individuals with AS [85]. Treatment with TNF-alpha inhibitors in patients with AS effectively reduces disease activity and alleviates fatigue.…”
Section: Fatigue In Ankylosing Spondylitismentioning
confidence: 99%